Applications of Bioadhesives: A Mini Review - Duan, Wanglin; Bian, Xiangbing; Bu, Yazhong (Frontiers in Bioengineering and Biotechnology, 2021)
Bioadhesives have demonstrated their superiority in clinical applications as tissue adhesives, hemostats, and tissue sealants. Because of the intrinsic stickiness, the applications have been expanded to various areas, such as functional wound dressing, factor delivery vehicles, and even medical device fixation. While many literature works discussed the mechanism of bioadhesives, few of them specifically summarized the applications of bioadhesives. To fill in the blanks, this review covers recent research articles and focuses precisely on the applications of bioadhesives which can be generally classified as follows: 1) wound closure, 2) sealing leakage, and 3) immobilization, including those already in the clinic and those showing great potential in the clinic. It is expected that this article will provide a whole picture on bioadhesives’ applications and lead to innovations in the application of bioadhesives in new fields.